(untitled) (Journal of Technology and Operations Management, 2024)
Nowadays, the world is facing a crisis of sustainability challenges and industries in developed countries are making strategies to respond to those challenges by implementing green supply chain management. To avoid this effect having a negative impact on the environment, of the various efforts taken by the firm among the steps are taken is to practice green practices in every operating activity of the supply chain way to reduce the impact on the environment. This study aims to present a systematic literature review of green supply chain management practices and examination of examine previous studies on green supply chain management. This study was conducted on the article data collected from the Web of Science (WOS) and Scopus databases between the years 2013 and 2023 using the Preferred Reporting Items for Systematics Review and Meta Analyses (PRISMA) approach. The final method consisted of screening 83 articles, and an analysis was carried out to look for patterns of article citation, prior research settings that are nation based and field study use studies in green supply chain. Furthermore, it indicates that the amount of empirical research work on green supply chain management has increased rapidly over the last few years. The development of green supply chain management is notably significant due to its diverse advantages, including improved economic performance, adherence to stakeholder expectations, and the opportunity for innovation via digital transformation. As organisations traverse the intricacies of contemporary supply chains, the incorporation of sustainability into their operations is more essential for enduring success.